2021
DOI: 10.3390/sports9010006
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Transition to a Vegan Diet in an Elite Male Gaelic Football Player

Abstract: Vegan diets are increasingly of interest to athletes, but require a well-planned approach in order to mitigate the risk of potential adverse effects on nutrient intakes, and consequently performance. This case study reports the process of an elite male Gaelic football player (age 25 years; height, 1.88 m; body mass, 87.8 kg; lean body mass, 73.26 kg; body fat, 11.3%) transitioning from an omnivorous diet to a vegan diet at the beginning of a competitive season. The report encompasses key considerations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…e experiment found that the ball speed was much lower than when kicked by the foot arches or the instep. ere was also a signi cant di erence in the rotation speed and torque of the ball kicked by the outer medullary joint and the outer instep [4]. Caetano et al studied football players' injury risks from heading through multiple heading tests on four adult men, former high school athletes.…”
Section: Related Workmentioning
confidence: 99%
“…e experiment found that the ball speed was much lower than when kicked by the foot arches or the instep. ere was also a signi cant di erence in the rotation speed and torque of the ball kicked by the outer medullary joint and the outer instep [4]. Caetano et al studied football players' injury risks from heading through multiple heading tests on four adult men, former high school athletes.…”
Section: Related Workmentioning
confidence: 99%
“…Pada dimensi kompetensi, ada yang dinamakan Contigency Management Skill yang di dalamnya merujuk pada strategi dalam mengelola sebuah masalah mulai dari memecahkan persoalan gagasan artistik dengan riset breakdown, studi bentuk, riset material untuk kebutuhan tokoh meliputi: kostum, hand property, setting properti, dan mood. Tahapan kedua yaitu penentuan desain, uji, dan strategi kasus menggunakan pendekatan studi kasus Yin dalam praktik produksi penata artistik yang dilakukan oleh sineas/kreator dengan menyiapkan tipe komponen riset sesuai dengan konteks diawali dengan: (1) Menyiapkan konsep pertanyaan dalam diri atau tim produksi tentang unsur kausalitas (bagaimana dan mengapa) untuk merasionalkan setiap elemen sinematografi; (2) Membimbing dalam pencarian data yang relevan tentang isu teoretis pada setiap konteks, tahapan ini disebut dengan proposisi; (3) Memecah unit analisis konteks sesuai kasus yang terjadi; (4) Tetap menjalankan prinsip logika antara data dan proposisi; (5) Membagi kriteria dari temuan tersebut (Davey et al, 2021). Pemilihan desain kasus perlu dilakukan untuk menjamin protokol dalam riset dapat terjadi dengan membagi item penelitian (analisis tunggal & multi analisis) berdasarkan workflow produksi dan menentukan uji kualitas kasus berdasarkan item yang dipilih (Gini et al, 2009), hal tersebut dapat terlihat pada Gambar 5.…”
Section: Hasil Dan Pembahasanunclassified
“…Currently, there is still a common belief in the general population that a vegan diet may be detrimental to endurance and muscle strength. Clinical and cross-sectional studies comparing vegan, lacto-ovo-vegetarian and omnivorous diets have shown comparable [18,[139][140][141][142] or better [143] aerobic capacity, anaerobic performance or muscle strength on a vegan diet [18,[139][140][141][142][143]. A recent narrative review of observational and interventional studies of young and competitive athletes on vegan diets showed that they are able to tolerate and sustain higher physical burdens for longer durations and to recover from physical stress more rapidly.…”
Section: Sport and Exercise Performancementioning
confidence: 99%
“…Numerous new challenges may arise with demanding changes in vegan dietary behavior. These challenges also include (i) social pressures (e.g., from family members, coworkers and friends who may not support individuals changing to a vegan diet), (ii) expected behaviors (e.g., associated with cultural norms), (iii) many logistical challenges (e.g., meal planning and food preparation), (iv) limited meal choices for a well-designed vegan diet when outside the home environment (e.g., balanced meals in a whole-food, plant-based diet) and (v) an urgent need to acquire new skills (e.g., organization and preparation of delicious balanced meals at home and away from home) with which to successfully change eating habits [18,98,174,327,328].…”
Section: Specific Characteristics Of a Vegan Diet/lifestylementioning
confidence: 99%
See 1 more Smart Citation